Descriptive overview of the 2011 epidemic of arboviral disease in horses in Australia. Issue 1 (19th December 2012) - Roche, SE; Wicks, R; Garner, MG; East, IJ; Paskin, R; Moloney, BJ; Carr, M; Kirkland, P
<x xml:space="preserve">Abstract</x> Objective To provide an overview and descriptive analysis of the 2011 arboviral disease epidemic in horses that involved three important Australian mosquito‐borne viruses: Murray Valley encephalitis virus, West Nile virus (Kunjin strain) and Ross River virus. Methods Data from states affected between January and June 2011 were collated and comprised reports of horses showing signs of neuromuscular disease and the associated laboratory findings. A summary of the data is presented, together with a spatiotemporal analysis of cases and preliminary assessment of rainfall patterns and case distribution. Results A total of 982 cases of equine arboviral disease were reported across Australia between January and June 2011. The majority of cases were reported from south‐east Australia and included horses that developed neurological signs consistent with encephalitis. It was the largest epidemic of equine arboviral disease in Australia's history. Two likely causes for this unprecedented epidemic were the unusual weather events that preceded the epidemic and the emergence of a new strain of Kunjin virus. Conclusions The epidemic highlights to horse owners and policy makers the potential for future outbreaks of arboviral diseases and the need for vigilance. It also highlights the complex interactions among hosts, vectors and climatic conditions that are required for such an outbreak to occur.